A cyclic (alkyl)(boryl)germylene derived from a cyclic (alkyl)(amino)germylene - Rao, Bin (2021)
A cyclic (alkyl)(amino)germylene undergoes a ring expansion reaction with dibromomesitylborane (MesBBr2 ) to afford a six-membered dibromogermane derivative. In the presence of Lewis bases (PMe3 or Me NHC), reduction of the latter with two equivalents of potassium graphite (KC8 ) gives rise to cyclic (alkyl)(boryl)germylene-Lewis base adducts. Upon heating, the germylene-PMe3 adduct reacts with H2 to yield a germane, probably via a base-free germylene featuring a small HOMO-LUMO gap.